The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00213-008-1170-3
|View full text |Cite
|
Sign up to set email alerts
|

Permanent improvement in deficient sensory inhibition in DBA/2 mice with increased perinatal choline

Abstract: These data show that gestational choline supplementation produces permanent improvement in a deficit associated with schizophrenia and may have implications for human prenatal nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 65 publications
7
48
1
Order By: Relevance
“…Conversely, choline deficiency during these sensitive periods results in altered memory function and associated cognitive deficits that also persist (Meck and Williams 1997c. Furthermore, recent studies suggest that perinatal choline supplementation can alleviate the cognitive effects of postnatal, human-third-semester pregnancy equivalent, alcohol exposure in rat offspring (e.g., Thomas et al 2000Thomas et al , 2004Thomas et al , 2007, and ameliorate brain growth factor and sensorimotor deficiencies in mouse models of schizophrenia and Rett syndrome (e.g., Nag and Berger-Sweeney 2007; Stevens et al 2008). The likely mechanism for these effects of choline involves an epigenetic change in DNA methylation, altered gene expression, and resulting changes in stem cell proliferation and differentiation (Zeisel 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, choline deficiency during these sensitive periods results in altered memory function and associated cognitive deficits that also persist (Meck and Williams 1997c. Furthermore, recent studies suggest that perinatal choline supplementation can alleviate the cognitive effects of postnatal, human-third-semester pregnancy equivalent, alcohol exposure in rat offspring (e.g., Thomas et al 2000Thomas et al , 2004Thomas et al , 2007, and ameliorate brain growth factor and sensorimotor deficiencies in mouse models of schizophrenia and Rett syndrome (e.g., Nag and Berger-Sweeney 2007; Stevens et al 2008). The likely mechanism for these effects of choline involves an epigenetic change in DNA methylation, altered gene expression, and resulting changes in stem cell proliferation and differentiation (Zeisel 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Choline deficiency during the same developmental time frame, embryonic days (ED) 12-17, results in impaired performance on some, but not all, of these behavioral measures (e.g., Williams 1999, 2003). Furthermore, perinatal choline supplementation can alter behavior following a variety of developmental disorders, including the alleviation of abnormalities associated with fetal alcohol syndrome in rats (Thomas et al 2000(Thomas et al , 2004(Thomas et al , 2007Wagner and Hunt 2006), attenuation of some of the motor deficits observed in a Mecp21 lox mouse model of Rett syndrome (Nag and BergerSweeney 2007), and the improvement of sensory gating in a DBA/2 mouse model of schizophrenia that exhibits reduced numbers of hippocampal a7 nicotinic receptors (Stevens et al 2008).…”
mentioning
confidence: 99%
“…In addition, mice treated during gestation with choline develop increased numbers of alpha7 receptors in the hippocampus [124]. Thus, DBA/2 mice that have deficient sensory inhibition and reduced numbers of alpha7 nicotinic receptors in the hippocampus showed an increased number of alpha7 receptors and improved sensory inhibition following prenatal choline supplementation [125].…”
Section: Pharmacological Approachesmentioning
confidence: 98%
“…As gestational choline supplementation enhances gating and cognition in adult offspring mice (Meck and Williams 2003;Stevens et al 2008Stevens et al , 2014 and increases rates of efficient sensory inhibition (P50 suppression) in human infants whose mothers' diets during pregnancy were supplemented with choline (Ross et al 2013), dietary choline supplementation has been promoted as a possible preventive intervention for cognitive deficits in individuals considered to be "at risk" for SZ (Corriveau and Glenn 2012;Freedman 2014). …”
Section: Introductionmentioning
confidence: 99%